How Google and others upset competition analysis: disruptive innovation and European competition law - Inge Graef; Sih Yuliana Wahyuningtyas; Peggy Valcke (International Telecommunications Society (ITS), 2014)
Because of the reliance on market analysis, current competition law may not be sufficiently fit for taking account of disruptive innovation which leads to the introduction of new products or services overthrowing existing markets. In the US, innovation has been given a more prominent place in competition analysis by way of recognizing the existence of 'innovation markets' and 'innovation competition' in, respectively, the 1995 Antitrust Guidelines for the Licensing of Intellectual Property and the 2010 US Merger Guidelines. Although a similar notion of 'competition in innovation' has been introduced in the EU in policy documents in the area of Article 101 TFEU, in merger review and abuse of dominance cases such a concept has not been applied yet. By giving insight into the way in which the different pillars of EU competition law deal with disruptive innovation, this paper aims to contribute to the debate on how competition policy could be more conducive towards innovation in dynamic industries.
Keywords: 330; Disruptive innovation; dynamic competition; restrictive agreements; merger review; abuse of dominance